2002
DOI: 10.1055/s-0037-1613083
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic Genotypes Are not Associated with Pre-eclampsia and Gestational Hypertension: Results from a Large Population-based Study and Systematic Review

Abstract: SummaryDNA samples collected as part of a large population-based casecontrol study were genotyped to examine the associations of five prothrombotic gene polymorphisms with pre-eclampsia (PE) and gestational hypertension (GH). The polymorphisms studied were: G1691A in Factor V (Factor V Leiden; FVL), prothrombin G20210A, methylenetetrahydrofolate reductase (MTHFR) C677T, plasminogen activator inhibitor-1 4G/5G and the platelet collagen receptor α2β1 C807T. A group of 404 women who developed PE were retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
2
11

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 63 publications
(49 reference statements)
6
109
2
11
Order By: Relevance
“…Nevertheless, the association is not seen in all studies and there are very few large population-based studies [25,26]. Finally to the best of our knowledge there are not studies presenting how preeclampsia and ABO/Rh systems are related in a Brazilian population.…”
Section: Introductionmentioning
confidence: 88%
“…Nevertheless, the association is not seen in all studies and there are very few large population-based studies [25,26]. Finally to the best of our knowledge there are not studies presenting how preeclampsia and ABO/Rh systems are related in a Brazilian population.…”
Section: Introductionmentioning
confidence: 88%
“…Most recently, the meta-analysis by Xia et al (95) reported that the TT genotype compared with the CC and CT genotypes carried a significantly greater risk of preeclampsia (by 76%) among Asian women only, whereas in Caucasian women this increased risk was not evident. It is worth noting however that a much greater number of large-scale studies in this area have been conducted within Asian populations with far fewer studies conducted in Caucasian populations; a factor that limits Sohda et al (87) 425 Japan 2·5 (1·3, 4·8) Grandone et al (88) 225 Italy 1·8 (1·0, 3·5) Kupferminc (96) 144 Israel 2·9 (1·0, 8·5) Powers et al (97) 237 Caucasian women 1·28 (0·58, 2·79) Kobashi et al (98) 316 Japan 0·68 (0·30, 1·55) Laivuori et al (99) 216 Finland 0·50 (0·14, 1·77) Rigo et al (100) 221 Caucasian women 1·13 (0·38, 3·37) Morrison et al (101) 404 Scotland 1·00 (0·55, 1·82) Prasmusinto et al (102) 112 Germany and Croatia 0·28 (0·03, 2·47) Pegoraro et al (103) 609 South African (Black) 0·62 (0·06, 6·90) Perez-Mutul et al (91) 325 Mexico 0·94 (0·59, 1·49) Williams et al (104) 304 Peru 1·6 (0·7, 3·8) Yilmaz et al (105) 111 Turkey 0·84 (0·26, 2·67) Also-Rallo et al (79) 165 Spain 0·73 (0·31, 1·76) Hernandez-Diaz et al (86) 154 USA/Canada 3·0 (1·2, 7·7) Stiefel et al (106) 584 Spain 0·92 (0·50, 1·71) the extent to which different populations can be compared. An additional limitation is that genotype-driven recruitment is generally not undertaken in these studies, a feature that is reflected by the relatively small numbers of pregnant women with the TT genotype being investigated and these raised the concern that many such studies may be statistically underpowered.…”
Section: Role Of the Mthfr Genotype In Determining The Risk Of Hypertmentioning
confidence: 99%
“…The evidence in the literature summarized also in a recent meta-analysis [73] suggests that severe preeclampsia but not mild preeclampsia is associated with trombophilias. Mainly severe preeclampsia is associated with FV Leiden mutation hyperhomocyteinemia, and deficiencies of protein S C and AT III (Table 1).…”
Section: Summary: Preeclampsia and Thrombophiliamentioning
confidence: 99%
“…Preeclampsia is a multigenetic disease, and there are important difference in prognosis and management between late mild preeclampsia and early onset severe disease. Most studies and a recent meta analysis [73] suggest that there is an association between thrombophilias and the development of severe preeclampsia but not in mild preeclampsia [73]. The low-pressure intervillous blood flow in the presence of a maternal hypercoagulable state may trigger fibrin deposition in the placenta and cause placental infarcts which may incite development of early severe disease.…”
Section: Summary: Preeclampsia and Thrombophiliamentioning
confidence: 99%